Preparation and Characterisation of Cross-Linked Sago Starch Phosphates - Hussin, Faridah (1998)
This project was conducted to study the production of cross-linked sago starch phosphate and to characterise the material produced. Sago starch was phosphorylated at various pHs (from 6 to 11) under a range of phosphate salt concentrations (sodium tripolyphosphate [STPP] [1 to 9%] and sodium trimetaphosphate [STMP] [1 to 4%]) and in the presence of various sodium sulfate concentrations (1 to 9%). The phosphorylation was carried out for 40 to 80 mins at temperatures varying from 27 to 50°C and heating time from 0.5 to 3 hrs at temperatures between 100 to 160°C. It was observed that the reaction pH and concentration of phosphate salts played a significant effect on the phosphorus (P) content, pasting profile, and paste clarity of the sago starch phosphates produced. The phosphorus content was found to increase as the pH and concentration of phosphate salts were increased under all conditions. However, the phosphorus contents were found to be below the standard (STPP [0.4%], STMP [0.04%], and a mixture of STPP and STMP [0.4%]), except when the concentration of STMP was above 1%. The pasting profile showed that at pH 9.5, treatment of sago starch with a mixture of 5% STPP and 2% STMP yielded the best cross-linked sago starch phosphate where it showed the lowest hot paste viscosity and the highest cold paste viscosity. Paste clarity measurements of the phosphorylated starches indicated that cross-linking had accelerated rapidly with STMP above pH 8, with STPP above pH 9, and with a mixture of the two above pH 6. Paste clarity measurements also showed that cross-linking began to accelerate at 5% and below STPP, and 2% and below STMP when sago starch was phosphorylated at pH 11 and 8, respectively. Judging from the paste properties, phosphorylation of sago starch at 27°C for 1 hr with a mixture of 5% STPP and 2% STMP at pH 9.5 in the presence of 5% sodium sulfate and then heating at 130°C for 2 hr is recommended. Cross-linked sago starch phosphate and commercial cross-linked waxy com starch (Mazaca 3543X and 3544X) showed similar pasting profile. However, cross-linked sago starch phosphate had higher degree of phosphorylation (Phosphorus content), degree of substitution, swelling power and solubility, paste clarity and gel strength. The water holding capacity and sediment volumes were similar to one of the cross-linked waxy com starches (Mazaca 3544X). Morphology studies showed that these modified starches retained their granule shape with minimal degree of starch damage.